Ensuring the competitiveness of logistics enterprises amidst the military development of Ukraine's economy - Khatser, Maxim; Mikhailik, Oleksandr (Management and Entrepreneurship: Trends of Development, 2024)
The article is devoted to the formation of new scientific solutions regarding the search for ways to ensure the competitiveness of logistics enterprises amidst the military development of Ukraine's economy. It has been proven that Ukrainian logistics enterprises have significant problems in ensuring their own competitiveness under the modern conditions of the national economic system's development. The given situation requires the development and implementation of a set of measures aimed at solving the problems of ensuring the competitiveness of enterprises in the logistics sphere of the Ukrainian economy. The article aims to identify and study the competitiveness challenges of logistics enterprises amidst the military development of Ukraine's economy. It also helps find ways to solve them and obtain better positions by domestic logistics enterprises in the highly competitive environment of Ukraine in the conditions of full-scale military operations against Russian war aggressors. Methodology: a complex of general and special methods have been used at the empirical and theoretical levels, such as the method of abstraction to determine the fundamental problems of ensuring the competitiveness of Ukrainian logistics enterprises; methods of analysis and synthesis for the development of a set of measures to ensure the competitiveness of logistics enterprises amidst military development of Ukraine's economy; methods of systematization, grouping and logical generalization for information systematization, conclusions formation, and scientific proposals of the article. The article uses system and functional, historical and systemic approaches in revealing and solving the problems of finding ways to ensure the competitiveness of Ukrainian logistics enterprises amidst the military development of the country's economy. Results: a set of measures to ensure the competitiveness of logistics enterprises in Ukraine in the conditions of the military development of the country's economy has been developed and proposed.JEL Classification: L 20, L 99, M 13